Microbial life at -13°C in the brine of an ice-sealed Antarctic lake - Murray, A.; Kenig, F.; Fritsen, C.; McKay, C.; Cawley, K.; Edwards, Peter; Kuhn, E.; McKnight, D.; Ostrom, N.; Peng, V.; Ponce, A.; Priscu, J.; et al. (National Academy of Sciences, 2012)
The permanent ice cover of Lake Vida (Antarctica) encapsulates an extreme cryogenic brine ecosystem (-13 °C; salinity, 200). This aphotic ecosystem is anoxic and consists of a slightly acidic (pH 6.2) sodium chloride-dominated brine. Expeditions in 2005 and 2010 were conducted to investigate the biogeochemistry of Lake Vida’s brine system. A phylogenetically diverse and metabolically active Bacteria dominated microbial assemblage was observed in the brine. These bacteria live under very high levels of reduced metals, ammonia, molecular hydrogen (H2), and dissolved organic carbon, as well as high concentrations of oxidized species of nitrogen (i.e., supersaturated nitrous oxide and ~1 mmol·L-1 nitrate) and sulfur (as sulfate). The existence of this system, with active biota, and a suite of reduced as well as oxidized compounds, is unusual given the millennial scale of its isolation from external sources of energy. The geochemistry of the brine suggests that abiotic brine-rock reactions may occur in this system and that the rich sources of dissolved electron acceptors prevent sulfate reduction and methanogenesis from being energetically favorable. The discovery of this ecosystem and the in situ biotic and abiotic processes occurring at low temperature provides a tractable system to study habitability of isolated terrestrial cryoenvironments (e.g., permafrost cryopegs and subglacial ecosystems), and is a potential analog for habitats on other icy worlds where water-rock reactions may cooccur with saline deposits and subsurface oceans.